2023
DOI: 10.2337/dc22-0772
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Benefits of Novel Diabetes Drugs by Baseline Cardiovascular Risk: A Systematic Review, Meta-analysis, and Meta-regression

Abstract: BACKGROUND Eligibility for glucagon-like peptide 1 receptor agonists (GLP-1RA) and sodium–glucose cotransporter 2 inhibitors (SGLT2i) has been expanded to patients with diabetes at lower cardiovascular risk, but whether treatment benefits differ by risk levels is not clear. PURPOSE To investigate whether patients with varying risks differ in cardiovascular and renal benefits from GLP-1RA and SGLT2i with use of meta-analysis a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…This result is also consistent with the "obesity paradox," in which overweight and mild to moderate obesity are associated with significantly higher survival in HF patients compared to normal-weight patients [24]. Previous studies have shown that the absolute benefit of SGLT2 inhibitors is increased in patients at high CV risk, particularly those HHF [25]. The combination of SGLT2 inhibitors and drugs that treat HF in patients with HF significantly reduces CV mortality, whereas SGLT2 inhibitors alone reduce HHF rates more than drugs which specifically aim to treat HF [26,27].…”
Section: Discussionsupporting
confidence: 84%
“…This result is also consistent with the "obesity paradox," in which overweight and mild to moderate obesity are associated with significantly higher survival in HF patients compared to normal-weight patients [24]. Previous studies have shown that the absolute benefit of SGLT2 inhibitors is increased in patients at high CV risk, particularly those HHF [25]. The combination of SGLT2 inhibitors and drugs that treat HF in patients with HF significantly reduces CV mortality, whereas SGLT2 inhibitors alone reduce HHF rates more than drugs which specifically aim to treat HF [26,27].…”
Section: Discussionsupporting
confidence: 84%
“…We expected a higher percentage of patients to be using medications with proven cardiovascular and renal benefits (SGLT2i, GLP-1r) in Cluster 3, as it had the highest percentage of patients with renal impairment and coronary heart disease 40 . These drug classes have shown superiority in terms of cardiovascular and renal outcomes compared to DPP4i in patients with T2DM, as demonstrated in a meta-analysis that included 23 cardiovascular outcome trials 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review using meta-nalysis and meta-regression evaluated the cardiovascular and renal benefits of GLP-1 RAs with the exception of tirzepatide [318]. For this purpose, 34 reports from 22 RCTs were analysed (9 GLP-RAs, 13 SGLT-2 inhibitor studies).…”
Section: Benefits Of Glp-1 Ras and Sglt-2 Inhibitors On Cardiovascula...mentioning
confidence: 99%
“…In the placebo group, the improvement was only 17 % (p < 0.001 for semaglutide 0.4 mg vs. placebo). However, neoplasia (benign, malignant or unspecified) was found in 15 % of patients ▶Table 6 Cardiovascular and renal benefits under therapy with GLP-1 receptor agonists and SGLT-2 inhibitors compared to placebo in a recent extensive meta-analysis [318].…”
Section: Incretin-based Therapies and Fatty Livermentioning
confidence: 99%